Variability and change in Palaeo-Eskimo architecture: A view from the Canadian High Arctic - Sutherland, Patricia (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2003)
AbstractThis paper explores the nature and causes of geographical and temporal variation in the architectural remains of Palaeo-Eskimo occupation in the High Arctic. It is suggested that much of the variability in the architectural record relates to local and situational factors rather than to cultural prescription. Three structural features — the box-hearth, midpassage and longhouse — are selected as representing a complex of elements with broad geographical and temporal distribution, and which may have had symbolic meaning related to Palaeo-Eskimo society and worldview. Changes in the form and distribution of these features are summarized, and the degree to which these variations may reflect social processes and historical events is examined.